Development of Teaching Materials for the Interpretation of the Tarbawi Hadith for Early Childhood Based on the Internalization of Islamic Values - Yunita, Yenni; Raihana, Raihana; Harahap, Musaddad; Namora, Dian (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The purpose of this study is to analyze the existing conditions of Tafsir and Hadith Tarbawi teaching materials, develop Tafsir Hadith Tarbawi teaching materials that are in line with the characteristics of early childhood learning, and test the effectiveness of the developed teaching materials in internalizing Islamic values for students of the early childhood Islamic education faculty of Islamic religion university of Riau. The type of research used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data sources in this study were students and lecturers. The population in this study was all students of Early Childhood Islamic Education, Faculty of Islamic Religion, Riau Islamic University, totaling 60 people. The sampling technique used was purposive sampling, by selecting 30 students. Data collection techniques through questionnaires, interviews, and observations. The data analysis technique used is quantitative descriptive analysis. The results of the study indicate that the teaching materials developed are effective in internalizing students' understanding of Islamic values and capable of shaping good character from an early age. This study is expected to make a significant contribution to the development of Islamic education for early childhood.